Exercise-induced hypoxemia predicts heart failure hospitalization and death in patients supported with left ventricular assist devices. Issue 3 (March 2020) - Koerber, Daniel M; Rosenbaum, Andrew N; Olson, Thomas P; Kushwaha, Sudhir; Stulak, John; Maltais, Simon; Behfar, Atta
Following implantation of continuous-flow left ventricular assist devices, mechanical off-loading results in improved resting hemodynamics; however, peak exercise capacity generally does not increase substantially. This study evaluated patients supported by continuous-flow left ventricular assist devices who were invasively monitored during exercise to define parameters that underpin exercise capacity and outcomes. A review of all patients supported by continuous-flow left ventricular assist devices who underwent supine bicycle ergometry exercise testing with measurement of pulmonary gas exchange during right heart catheterization for evaluation of dyspnea at one institution between 2007 and 2018 was performed (n = 22). The primary outcome of this investigation was death or heart failure hospitalization. Although resting filling pressures were relatively preserved, resting cardiac index (Fick) was low (2.1 ± 0.5 mL/kg/min). An impaired cardiac output reserve was present in 75% of patients. On univariate modeling, patients with supine exercise–induced hypoxemia (O2 saturation <90%) experienced significantly diminished hospitalization-free survival (unadjusted hazard ratio = 11.0, confidence interval = 2.4–57.2, p = 0.003), which persisted despite adjustment for right heart catheterization peak VO2 and peak cardiac output (adjusted hazard ratio = 25, confidence interval = 3.6–322, p = 0.001). Our findings suggest that supine exercise testing provides additional prognostic utility in the continuous-flow left ventricular assist device population.